The Commedia dell'Arte in the English imagination, 1571-1611 - Roberts, T; Das, N (2020)
This thesis examines how the commedia dell’arte manifested in the English imagination in the period 1571-1611. This form of professional, semi-improvised performance practice emerged from Italy in the mid-sixteenth century to capture the hearts of audiences across Europe and introduce regional dramaturgies to the literary and theatrical innovations of the Cinquecento. There are frequent references to the masked stock characters and extemporising routines of the arte in extant English print, and scholars have often found parallels between the dramas and performance practices of English playwrights and Italian practitioners. However, these studies are complicated by the lack of direct exposure to the arte in performance. The Italians made only a handful of visits to England in the 1570s, after which they would not set foot on English soil again for over twenty years.